Combining approach bias modification with working memory training during inpatient alcohol withdrawal: an open-label pilot trial of feasibility and acceptability - Victoria Manning; Katherine Mroz; Joshua B. B. Garfield; Petra K. Staiger; Kate Hall; Dan I. Lubman; Antonio Verdejo-Garcia (BMC, 2019)
Abstract Background According to contemporary neurocognitive models, addiction is maintained by the biasing of information-processing and decision-making systems towards relatively automatic, impulsive, reward-seeking responses to drug-related stimuli, and away from more controlled, deliberative, "reflective" states of processing that could result in decisions to delay or avoid drug use. Cognitive training programs aimed at either countering "impulsive" processing or enhancing "reflective" processing alone have shown promise. However, there has been no attempt to simultaneously target both aspects of processing with a combined training program. We aimed to test the feasibility and acceptability of a novel 'dual-training' program targeting both processes during residential alcohol withdrawal, and to measure abstinence rates following discharge. Methods Thirty-seven patients undergoing alcohol withdrawal at a residential unit participated in this open-label pilot feasibility study. We tested a 4-session program of dual cognitive training targeting both impulsive (approach bias) and reflective (working memory) aspects of processing. Descriptive statistics were used to examine feasibility (training uptake and completion rates) and acceptability (withdrawal from the study; participants' ratings of the tasks). Alcohol abstinence rates were examined 2-weeks post-discharge. Results Seven participants withdrew after commencing training. Twenty-six (70%) completed the 4-session training protocol, and four completed 3 sessions before discharging. Among participants who provided ratings, nearly all (93%) rated the training as interesting. Most (87%) indicated that they felt it had improved their attention. However, most did not feel it had decreased their craving for alcohol. At 2-weeks post-discharge, 16 (53%) participants reported abstaining from alcohol. For comparison, an earlier pilot trial in the same setting found a 68% abstinence rate with approach bias training alone, and 47% abstinence in a non-training control group. Conclusions Dual training during residential alcohol detoxification appears to be both acceptable and feasible, suggesting that future research is warranted to test its effectiveness at reducing likelihood of relapse.